Trustwide Clinical Audit of Dementia Diagnosis: How Are Diagnoses Made and What Treatments Are Offered? - Olusegun Sodiya; Oluwatosin Atewogboye; Roseline Ataria; Mani Krishnan; Rachael Raw (BJPsych Open)
Aims: To assess variations in dementia treatment, diagnosis, and pathway practices across the memory services in Tees, Esk and Wear Valleys (TEWV) NHS Foundation Trust and how these compare to Trust and national policy. There were reports that the dementia diagnostic process across the trust was inconsistent. Thus, it was important to find out if the diagnostic pathway differed. NICE guidelines NG97 (2018) recommended neuroimaging, cognitive testing, and history to make diagnosis and the use of validated criteria to diagnose dementia subtypes. NG97 (2018) and TEWV Dementia Pathway suggested use of cholinesterase inhibitors to those with Alzheimer’s disease, mixed dementia, dementia with Lewy bodies and Parkinson’s disease dementia. These guidelines mentioned that memantine should be offered to those with severe Alzheimer’s, or those with moderate Alzheimer’s disease with a contraindication to cholinesterase inhibitors.